Mesangiogenic progenitor cells: a mesengenic and vasculogenic branch of hemopoiesis? A story of neglected plasticity - Pacini, Simone (Frontiers in Cell and Developmental Biology, 2025)
Mesangiogenic progenitor cells (MPCs) are mesengenic and vasculogenic cells isolated from human bone marrow mononuclear cell cultures. Although MPCs were first described over two decades ago and have demonstrated promising differentiation capabilities, these cells did not attract sufficient attention from experts in the field of tissue regeneration. Several reports from the first decade of the 2000s showed MPC-like cells co-isolated in primary mesenchymal stromal cell (MSC) cultures, applying human serum. However, in most cases, these rounded and firmly attached cells were described as “contaminating” cells of hemopoietic origin. Indeed, MPC morphology, phenotype, and functional features evoke but do not completely overlap with those of cultured peripheral macrophages, and their hemopoietic origin should not be excluded. The plasticity of cells from the monocyte lineage is surprising but not completely unprecedented. Underestimated data demonstrated that circulating monocyte/macrophages could acquire broader plasticity under specific and different culture conditions, and this plasticity could be a consequence of in vitro de-differentiation. The evidence discussed here suggests that MPCs could represent the cell identity toward which the de-differentiation process reprograms the circulating mature phagocytic compartment.